2019
DOI: 10.1111/eth.12975
|View full text |Cite
|
Sign up to set email alerts
|

Multiple behavioral contexts of a melanized tail display in a desert lizard

Abstract: Conspicuous color displays in animals are often studied in the context of how they communicate an individual's reproductive value, ability to escape capture, or overall health. The study of sexual dichromatism often focuses on the evolution of male display traits balanced between detectability and mate acquisition, representing constraints stemming from both natural and sexual selection. Melanistic coloration and melanin color patterns play important roles in both intraspecific and interspecific signaling in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…48 Tail displays in lizards 49 might have the function of predator deterrence. 49 Gilbert et al 50 showed that multiple behavioral contexts are related to tail display in lizards, similar to tail flicking in birds, assuming that this would be another field for a meta-analytic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…48 Tail displays in lizards 49 might have the function of predator deterrence. 49 Gilbert et al 50 showed that multiple behavioral contexts are related to tail display in lizards, similar to tail flicking in birds, assuming that this would be another field for a meta-analytic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We used ceramic bulbs to ensure visible lighting was uniform throughout the arena (as lighting was uniform in the UV treatment, see below). We affixed a thermocouple (type T, 5SC series, 40‐gauge) to the cloacal surface of each lizard using a 1 × 1 cm piece of surgical tape (Gilbert et al, 2020; Muñoz & Losos, 2018). Each thermocouple was interfaced to an OMEGA™ 8‐channel data logger set to record temperatures at 30‐s intervals for the duration of a trial (60 min).…”
Section: Methodsmentioning
confidence: 99%